Low-residue diet with oral nutritional supplements prior to colonoscopy improves the quality of bowel preparation: an endoscopist-blinded, randomized controlled trial - Huilin Shen; Yijie Sun; Jin Qian; Jiaqi Wu; Xueqing Zhong; Guodong Li; Weimin Li (BMC Gastroenterology)
Abstract Background Poor bowel preparation has been a great problem of endoscopists for a long time. Low-residue diet (LRD) is often recommended on the day before colonoscopy. However, the quality of bowel preparation with LRD alone is suboptimal. The aim of our study was to examine whether patients who consumed LRD with oral nutritional supplements (ONSs) had higher quality of bowel preparation than patients who consumed LRD alone before colonoscopy. Methods An endoscopist-blinded, randomized controlled trial was conducted in inpatients who scheduled for colonoscopy with sedation. Patients were randomized to the non-ONS group and the ONS group. The primary outcomes were the rates of adequate bowel preparation measured by the Boston Bowel Preparation Scale (BBPS), the Ottawa Bowel Preparation Scale (OBPS) and the Colon Endoscopic Bubble Scale (CEBuS). The secondary outcomes were the adenoma detection rate (ADR), polyp detection rate (PDR), intubation time, withdrawal time and rates of adverse events. Results In both groups, 100 patients were analyzed. The rates of adequate bowel preparation measured by the BBPS and OBPS and PDR were significantly higher in the ONS group than in the non-ONS group (all P < 0.05). However, no significant differences were observed in the CEBuS scores, ADR, intubation time and rates of adverse events between the two groups (all P > 0.05). The withdrawal time was longer in the non-ONS group than the in the ONS group (P < 0.05). Conclusions LRD with ONSs helps increase the quality of bowel preparation. To help with colorectal cancer (CRC) screening, further studies are warrant. Trial registration [Chinese Clinical Trial Registry], [ChiCTR2400091660], [31/10/2024], [Retrospectively registered]